Preparation of organic compound modified spinel catalyst and method for selective catalytic reduction of nitrogen oxide
The preparation of organic compound-modified spinel catalysts through solution combustion solves the problem of insufficient catalytic activity and stability, and achieves efficient selective catalytic reduction of nitrogen oxides, which is suitable for industrial production.
Patent Information
- Application Number
- CN202510644851.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-08-22
AI Technical Summary
When existing spinel catalysts catalyze nitrogen oxides, their catalytic activity and stability are insufficient, making them difficult to meet increasingly stringent environmental protection requirements, and the preparation process is complicated, which is not conducive to large-scale industrial production.
The spinel catalyst modified with organic compound was prepared by solution combustion. The modified spinel catalyst was formed by doping organic compounds such as citric acid, polyethylene glycol, D-L alanine and polyvinyl alcohol to improve catalytic activity and stability.
The prepared catalyst exhibits a large specific surface area and pore volume, provides a rich active center, and improves the performance of selective catalytic reduction of nitrogen oxides, especially at low temperatures.
Smart Images

Figure CN120515428A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nitrogen oxide purification, and particularly relates to a method for preparing an organic compound modified spinel catalyst and catalytically oxidizing nitrogen oxides. Background Art
[0002] With the acceleration of industrialization, nitrogen oxides (NO x ) is one of the main air pollutants, posing a serious threat to the environment and human health. There are many types of nitrogen oxides, mainly including nitric oxide (NO), nitrogen dioxide (NO2), etc. These substances mainly come from fuel combustion, such as automobile exhaust, industrial kiln exhaust, etc. x It not only causes environmental problems such as acid rain and photochemical smog, but also harms the human respiratory and cardiovascular systems. Therefore, the development of efficient nitrogen oxide purification technology is of great practical significance.
[0003] Among the many nitrogen oxide removal technologies, selective catalytic reduction (SCR) denitrification has garnered widespread attention due to its high efficiency, energy-saving, and environmentally friendly advantages. This method uses a catalyst to convert nitrogen oxides into harmless nitrogen (N2) and water (H2O), achieving efficient nitrogen oxide removal. The core of this technology lies in the catalyst, and the development of high-performance catalysts is crucial to improving nitrogen oxide control efficiency.
[0004] Spinel-type catalysts are gradually coming into the spotlight as a promising catalyst type. The general formula of the spinel structure is AB2O4, where A and B are typically metal ions. This structure endows the catalyst with unique physicochemical properties, typically resulting in a high specific surface area and abundant active sites. These catalysts can effectively adsorb and activate reactant molecules, thereby improving the efficiency of the catalytic reaction and demonstrating certain advantages in the field of catalysis. For example, some spinel-type catalysts can maintain structural stability in certain reactions, preventing significant aging phenomena such as sintering or hydration. They can also provide abundant active sites to adsorb reactants and promote the reaction. However, conventional spinel catalysts still have some shortcomings in the catalytic oxidation of nitrogen oxides. On the one hand, their catalytic activity needs to be further improved to meet increasingly stringent environmental protection requirements and achieve more efficient nitrogen oxide removal. On the other hand, the stability of the catalyst also needs to be enhanced to ensure that it can continue to exert its catalytic effect stably and over a long period of time under complex actual operating conditions, such as varying temperatures, humidity, and environments containing a variety of impurity gases.
[0005] In order to overcome these shortcomings, researchers have tried to modify spinel catalysts through various methods. Among them, modification with organic compounds is an effective approach. Organic compounds can interact with spinel catalysts in various ways, such as forming surface complexes, changing the surface electronic structure of the catalyst, introducing new active sites, etc. These modification methods can significantly improve the activity, selectivity and stability of the catalyst, thereby improving its performance in the catalytic oxidation of nitrogen oxides. At present, although there have been some research reports on organic compound modified catalysts, there is still a lot of room for research in terms of optimization of preparation process, stability of modification effect and in-depth understanding of reaction mechanism. For example, some preparation methods are relatively complicated and not conducive to large-scale industrial production; the modification effect of some modified catalysts will gradually weaken during long-term use. Therefore, it is of great practical significance to develop an efficient, stable and simple preparation process of organic compound modified spinel catalyst and its catalytic oxidation method for nitrogen oxides.
[0006] Citric acid is a colorless, translucent, or white, odorless, acidic, and somewhat deliquescent chemical. It has three notable characteristics: first, it produces a non-aqueous substance upon crystallization in hot water; second, it crystallizes in ice-cold water; and third, the monohydrate product decomposes into an insoluble substance at temperatures between 77 and 90°C. Citric acid is soluble at temperatures between 15 and 20°C, and is also soluble in anhydrous ethanol. Structurally, citric acid is a tricarboxylic acid, and its physical and chemical properties are very similar to those of other carboxylic acids. Citric acid is a strong organic acid, with three carboxyl groups and one hydroxyl group in its molecular formula, which provides good coordination capabilities. Heating decomposes it into a variety of products, and it reacts with acids, bases, glycerol, and other substances.
[0007] Polyethylene glycol, abbreviated as "PEG," is a high molecular weight compound. PEG is formed by the polymerization of poly(ethylene epoxide) and water under the action of a catalytic material. As the molecular weight increases, its water solubility decreases, its vapor pressure decreases, its water absorption deteriorates, and its solubility in organic solvents decreases. The freezing point, relative density, flash point, and viscosity also increase accordingly. This is because the increase in molecular weight leads to an increase in the number of hydroxyl groups on the molecular chain segments, increasing the spatial distance between the hydrophilic and lipophilic groups in the molecule. When these groups approach each other, hydrogen bonds or van der Waals forces are formed, making PEG more easily dispersed in water, diffusing more slowly and less likely to form flocculent precipitates. PEG behaves as a pseudoplastic fluid in water, exhibiting good thermal stability, dispersibility, and wettability.
[0008] DL-Alanine is a racemic mixture of D-Alanine and L-Alanine. In recent years, it has been widely used in the synthesis of amino acids. It can be combined with metal elements and used as a raw material for the synthesis of other unnatural amino acids. It is also used for crystal structure studies using spectroscopic methods.
[0009] Polyvinyl alcohol (PVA) is a water-soluble polymer compound obtained by polymerization and alcoholysis (or hydrolysis) of vinyl acetate. Its molecular structure is [CH2CH(OH)] n The distribution and content of hydroxyl (-OH) groups in the molecular chain can be controlled by the degree of alcoholysis, resulting in a series of products with varying degrees of polymerization and alcoholysis. In industry and research, polyvinyl alcohol (PVA) has become one of the most widely used polymer materials due to its unique water solubility, film-forming properties, adhesion, and biocompatibility. In the chemical industry, PVA is an important raw material used in the synthesis of other high-value-added compounds. It can react with a variety of chemical reagents to produce derivatives with unique properties. Summary of the Invention
[0010] The problem to be solved by the present invention is the development of an organic compound modified spinel catalyst for the selective catalytic reduction of nitrogen oxides.
[0011] The present invention discloses a method for preparing an organic compound modified spinel catalyst and selective catalytic reduction of nitrogen oxides, comprising the following steps: The present invention utilizes a solution combustion method to prepare an organic compound-modified spinel catalyst: (1) All the raw materials used in the experiment, including citric acid, polyethylene glycol (PEG-4000), DL-alanine, polyvinyl alcohol, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and chromium nitrate nonahydrate, were of analytical grade. The reaction equations for cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and chromium nitrate nonahydrate are: 0.1Ce(NO3)3+0.9Co(NO3)2+2Cr(NO3)3→Ce 0.1 Co 0.9 Cr2O4+4.05N2+10.15O2 (2) Weigh a certain amount of analytically pure Co(NO3)2·6H2O, analytically pure Ce(NO3)3·6H2O, and analytically pure Cr(NO3)3·9H2O into a beaker, add 100 ml of deionized water, and stir in a constant temperature water bath at 75-85°C until completely mixed. (3) Citric acid, polyethylene glycol 4000, DL-alanine, and polyvinyl alcohol were added to three beakers at a molar ratio of 1.5:1 between the organic compound and the metal nitrate, and appropriate amount of deionized water was added. The mixture was stirred in a constant temperature water bath at 75-85°C until completely mixed. (4) The sample without adding organic compounds was named as the no-addition sample as the blank control group; (5) Add metal nitrate solution to the sample solutions of citric acid, polyethylene glycol 4000, DL-alanine, and polyvinyl alcohol, respectively, and continue heating and stirring in a water bath for 1 h; (6) stirring the resulting solution at a temperature of 65-70° C. until it reaches a viscous syrupy consistency; (7) transferring it to a preheated oven at 190-220°C for 1-2 hours to decompose the citric acid precursor; (8) The obtained solution is transferred to a constant temperature drying oven at 70-80°C and dried to a viscous gel. The sample is then transferred to a muffle furnace and burned at 600-650°C. After cooling to room temperature, the sample is taken out to obtain an organic-doped spinel catalyst precursor powder. (9) Grind the powder obtained from the combustion at room temperature using a mortar and pestle to prepare the sample. After the prepared drug is placed in an ampoule, the drug is numbered according to the drug mass required for different measurements and a regular control group is designed for characterization and performance measurement.
[0012] Beneficial effect: Compared with the reported method for preparing spinel catalyst (1) The DL-alanine modified spinel catalyst prepared by the present invention has good catalytic performance for the selective catalytic reduction of nitrogen oxides. The prepared catalytic material presents a typical IV type isotherm and H3 type hysteresis loop, which indicates that the prepared catalytic material presents a disordered mesoporous structure. When P / P0 is between 0.8 and 1, the H3 loop indicates that the sample contains flake-like aggregated nanoparticles, forming slit-like pores. It can be seen that the hysteresis loop of the DL-alanine modified spinel catalyst is larger, indicating that the number of pores is larger. From the specific surface area (S BET ) and total pore volume (V p ) Parameter summary shows that the specific surface area and total pore volume of the DL-alanine modified spinel catalyst are significantly larger than those of other catalysts, indicating that the addition of PVA has a certain effect on the specific surface area and pore volume of Co3O4; (2) Experimental data show that the polyacidic sites in the spinel catalyst modified by organic compounds provide abundant active centers; (3) The NH3-TPD test results show that the spinel catalyst modified by organic compounds exhibits multiple discontinuous NH3 desorption peaks, indicating the existence of different NH3 adsorption sites. There is an obvious NH3 desorption peak near the DL-alanine modified spinel catalyst at around 212 °C, corresponding to the weak NH3 desorption peak. 4+ and Desorption of NH3 coordinated by the acid sites demonstrates the excellent low-temperature SCR performance of the DL-alanine-modified spinel catalyst. In O2-TPD analysis, two peaks were observed for all spinel catalysts modified with organic compounds. The DL-alanine-modified spinel catalyst exhibited the highest surface oxygen desorption, a lower desorption temperature, and the highest desorption amount, indicating that the recombination of oxygen at the active sites enhances O2 desorption, thereby improving the selective catalytic reduction performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is an X-ray diffraction pattern of the catalytic material of the present invention; Figure 2 This is a SEM image of the catalytic material of the present invention; Figure 3 A nitrogen adsorption-desorption curve diagram of the catalytic material of the present invention; Figure 4 is a diagram of the physical properties of the catalytic material of the present invention; Figure 5 NH3-TPD diagram of the catalytic material performance of the present invention; Figure 6 This is an O2-TPD diagram of the catalytic material performance of the present invention; Figure 7 This is a flow chart of the experimental preparation of the catalytic material of the present invention. DETAILED DESCRIPTION
[0014] In order to make the technical solution of the present invention clear and understandable, the technical solution of the present invention is described in detail and completely below.
[0015] Example 1: Selective catalytic reduction of nitrogen oxides by doping citric acid in spinel catalytic materials The preparation method is as follows: (1) The reaction equations for cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and chromium nitrate nonahydrate are: 0.1Ce(NO3)3+0.9Co(NO3)2+2Cr(NO3)3→Ce 0.1 Co 0.9 Cr2O4+4.05N2+10.15O2 (2) Weigh a certain amount of analytically pure Co(NO3)2·6H2O, analytically pure Ce(NO3)3·6H2O, and analytically pure Cr(NO3)3·9H2O into a beaker, add 100ml to 150ml of deionized water, and stir in a constant temperature water bath at 80℃ until fully mixed; (3) Add citric acid to three beakers at a molar ratio of 1.5:1 between the organic compound and the metal nitrate, add an appropriate amount of deionized water, and stir in a constant temperature water bath at 80°C until fully mixed; (4) Add metal nitrate solution to the citric acid sample solution and continue heating and stirring in a water bath for 1 h; (5) stirring the resulting solution at a temperature of 65-70° C. until it reaches a viscous syrupy consistency; (6) transferring it to a preheated oven at 190-220°C for 1-2 hours to decompose the citric acid precursor; (7) The obtained solution is transferred to a constant temperature drying oven at 70-80°C and dried to a viscous gel. The sample is then transferred to a muffle furnace and burned at 600-650°C. After cooling to room temperature, the sample is taken out to obtain an organic-doped spinel catalyst precursor powder. (8) Grind the powder obtained from the combustion at room temperature using a mortar and pestle to prepare the sample. After the prepared drug is placed in an ampoule, the drug is numbered according to the drug mass required for different measurements and a regular control group is designed for characterization and performance measurement.
[0016] Example 2: Polyethylene glycol is doped into a spinel catalytic material for selective catalytic reduction of nitrogen oxides. The preparation method is the same as that of Example 1, except that the citric acid in the organic compound is replaced with polyethylene glycol.
[0017] Example 3: DL-alanine is doped into a spinel catalytic material for selective catalytic reduction of nitrogen oxides. The preparation method is the same as that of Example 1, except that the citric acid in the organic compound is replaced by DL-alanine.
[0018] Example 4: Polyvinyl alcohol is doped into the spinel catalytic material for selective catalytic reduction of nitrogen oxides. The preparation method is the same as that of Example 1, except that the citric acid in the organic compound is replaced by polyvinyl alcohol.
[0019] Example 5: Selective catalytic reduction of nitrogen oxides by spinel catalytic material. The preparation method is the same as that of Example 1, except that citric acid as an organic compound is not added to prepare a blank control group.
[0020] Result detection (1) Scanning electron microscopy (SEM) Scanning electron microscopy (SEM) uses a focused high-energy electron beam to scan a sample, collect, amplify, and image different physical information on the sample surface. It is an electron microscopy technique that characterizes the microscopic morphology of the sample surface. The operation used a German ZEISS GeminiSEM300 instrument and an OXFORD XPLORE30 energy spectrometer. A small amount of sample was directly attached to the conductive adhesive and gold was sprayed using a Quorum SC7620 sputter coater for 45-50 seconds at 10-15 mA. The sample morphology was then photographed and energy spectrum mapped using a Zeiss GeminiSEM300 scanning electron microscope. The accelerating voltage for morphology photography was 2-3 kV, and the accelerating voltage for energy spectrum mapping was 15-16 kV. The detector was an SE2 secondary electron detector. The spinel catalysts of Examples 1 to 5 were subjected to scanning electron microscopy (SEM) testing, and the test results are shown in the figure. The scanning SEM images show that all spinel phases have consistent particle morphology and uniform particle size; (2) Specific surface area test method (BET) BET physical analyzer measures the surface area and pore structure of materials by utilizing the catalytic properties of solid materials. It can test the adsorption and desorption curves, pore size distribution, total pore volume, surface area and other data of the materials. The BET surface area and pore structure of the catalytic materials were characterized using a Quantachrome AUTOSORB IQ instrument with automated surface area, micropore size, and chemical catalytic analysis. Nitrogen was used as the catalytic gas, with He as the carrier gas. The materials were first degassed at 179–185°C for 6–7 hours, followed by catalytic nitrogen addition at -179–-185°C. The pore volume, pore size, and specific surface area of the catalytic materials were then calculated for a range of materials. (3) Ammonia temperature-programmed desorption (NH3-TPD) The NH3-TPD test results show that the organic compound modified spinel catalyst exhibits multiple discontinuous NH3 desorption peaks, indicating the existence of different NH3 adsorption sites. Combined with the SEM images, it can be inferred that the fluffy structure of the organic compound spinel catalyst provides abundant Lewis and There is an obvious NH3 desorption peak near the spinel catalyst modified with DL-alanine at 212℃, corresponding to the weak NH 4+ and The acid-coordinated NH3 desorption explains the excellent low-temperature SCR performance of the DL-alanine-modified spinel catalyst; (4) X-ray diffraction (XRD) The crystallinity of the spinel catalyst was determined by XRD. The results are shown in the figure. The XRD patterns of the samples are similar, all of which are face-centered cubic spinel Co3O4 (JCPDS No. 22-1084). The diffraction peaks at 19.1°, 31.3°, 36.8°, 44.9°, 55.7°, 59.2°, and 65.2° can be represented as (111), (220), (311), (400), (422), (511), and (440) reflections, respectively. At the same time, the high peak intensity confirms the high crystallinity of the sample. (5) Oxygen temperature programmed desorption (O2-TPD) In the O2-TPD analysis, two peaks were observed for the spinel catalysts modified with organic compounds. The peak observed between 60 and 240 °C corresponds to the oxygen on the catalyst surface, such as O 2- or O - The desorption of O2 is observed at 240°C, while the peak observed above 240°C corresponds to the desorption of lattice oxygen from Co3O4. The DL-alanine-modified spinel catalyst has the highest surface oxygen desorption amount and exhibits a lower desorption temperature and the highest desorption amount, indicating that the recombination of O2 on the active site enhances the desorption of O2, thereby improving the performance of selective catalytic reduction.
[0021] Obviously, the above embodiments of the present invention are only examples to clearly illustrate the present invention, and are not limited to the implementation methods. Ordinary technicians in the relevant field can make different forms of changes or modifications based on this, and there is no need to list all the implementation methods. At the same time, the general description and specific embodiments above are only used to illustrate the technical solutions of the present invention and are not limiting. Even with reference to the detailed description of the above embodiments, ordinary technicians in this field can still modify the technical solutions of each embodiment or replace some technical features with equivalents. As long as these modifications or replacements do not depart from the spirit and scope of the technical solutions of the embodiments of the present invention, they are all included in the scope of protection of the claims of the present invention.
Claims
1. An organic compound modified spinel catalyst, characterized in that Modification of Ce with four different organic compounds 0.1 Co 0.9 Cr2O4 spinel, the organic compounds are citric acid, polyvinyl alcohol, polyethylene glycol, and DL-alanine.
2. The spinel catalyst modified by an organic compound according to claim 1, wherein The types of the organic compounds are citric acid, polyvinyl alcohol, polyethylene glycol and DL-alanine.
3. The present invention discloses a method for preparing an organic compound-modified spinel catalyst and selective catalytic reduction of nitrogen oxides, comprising the following steps: The present invention utilizes solution combustion method to prepare spinel catalyst modified by organic compound (1) All the raw materials used in the experiment, including citric acid, polyethylene glycol (PEG-4000), DL-alanine, polyvinyl alcohol, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and chromium nitrate nonahydrate, were of analytical grade. The reaction equations for cobalt nitrate hexahydrate, cerium nitrate hexahydrate, and chromium nitrate nonahydrate are: <h2 style=";text-align:left;direction:ltr">0.1Ce(NO3)3+0.9Co(NO3)2+2Cr(NO3)3→Ce<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Co<h2 style=";text-align:left;direction:ltr"> 0.9 <h2 style=";text-align:left;direction:ltr"> Cr2O4+4.05N2+10.15O2 (2) Weigh a certain amount of analytically pure Co(NO3)2·6H2O, analytically pure Ce(NO3)3·6H2O, and analytically pure Cr(NO3)3·9H2O into a beaker, add 100ml to 150ml of deionized water, and stir in a constant temperature water bath at 75-85℃ until completely mixed; (3) Citric acid, polyethylene glycol 4000, DL-alanine, and polyvinyl alcohol were added to three beakers at a molar ratio of 1.5:1 between the organic compound and the metal nitrate, and appropriate amount of deionized water was added. The mixture was stirred in a constant temperature water bath at 75-85°C until completely mixed. (4) The sample without adding organic compounds was named as the no-addition sample as the blank control group; (5) Add metal nitrate solution to the sample solutions of citric acid, polyethylene glycol 4000, DL-alanine, and polyvinyl alcohol, respectively, and continue heating and stirring in a water bath for 1 h; (6) stirring the resulting solution at a temperature of 70-80° C. until it reaches a viscous syrupy consistency; (7) transferring it to a preheated oven at 190-220°C for 1-2 hours to decompose the precursor; (8) The obtained solution is transferred to a constant temperature drying oven at 70-80°C and dried to a viscous gel. The sample is then transferred to a muffle furnace and burned at 600-650°C. After cooling to room temperature, the sample is taken out to obtain an organic-doped spinel catalyst precursor powder. (9) Grind the powder obtained by combustion with a mortar and pestle at room temperature to prepare the sample. After the prepared drug is placed in an ampoule, the drug is numbered according to the drug mass required for different measurements and a regular control group is designed for characterization and performance measurement; (10) Scanning electron microscopy (SEM) Scanning electron microscopy (SEM) uses a focused high-energy electron beam to scan a sample, collect, amplify, and image different physical information on the sample surface. It is an electron microscopy technique that characterizes the microscopic morphology of the sample surface. The operation used a German ZEISS GeminiSEM300 and an OXFORD XPLORE30 spectrometer. A small amount of sample was directly attached to the conductive adhesive and gold was sprayed using a Quorum SC7620 sputter coater for 45-50 seconds at 10-15 mA. The sample morphology was then photographed and analyzed for energy spectrum using a Zeiss GeminiSEM300 scanning electron microscope. The accelerating voltage for morphology photography was 2-3 kV, and for energy spectrum mapping was 15-16 kV. The detector was an SE2 secondary electron detector. The spinel catalysts of Examples 1 to 5 were subjected to scanning electron microscopy (SEM) testing. The test results are shown in the figure. The scanning SEM images show that all spinel phases have consistent particle morphology and uniform particle size. (11) Specific surface area test method (BET) BET physical analyzer measures the surface area and pore structure of materials by utilizing the catalytic properties of solid materials. It can test the adsorption and desorption curves, pore size distribution, total pore volume, surface area and other data of the materials. The BET surface area and pore structure of the catalytic materials were characterized using a Quantachrome AUTOSORB IQ instrument with automatic surface area, micropore size, and chemical catalytic analysis. N₂ was used as the catalytic gas and He as the carrier gas. The materials were first degassed at 179–185°C for 6–7 hours and then catalyzed in N₂ at -179–-185°C. The pore volume, pore size, and specific surface area of the catalytic materials were then calculated. (12) Ammonia temperature programmed desorption (NH3-TPD) The NH3-TPD test results show that the spinel catalyst modified by organic compounds exhibits multiple discontinuous NH3 desorption peaks, indicating the existence of different NH3 adsorption sites. Combined with the SEM images, it can be inferred that the fluffy structure of the spinel catalyst provided abundant Lewis and There is an obvious NH3 desorption peak near the spinel catalyst modified with DL-alanine at around 212℃, corresponding to the weak NH 4+ and The acid-coordinated NH3 desorption explains the excellent low-temperature SCR performance of the DL-alanine-modified spinel catalyst; (13) X-ray diffraction (XRD) The crystallinity of the spinel catalyst was tested by XRD. The test results are shown in the figure. The XRD pattern in the figure shows diffraction peaks on the (111), (220), (311), (400), (422), (511) and (440) crystal planes with 2θ values of 19.1°, 31.3°, 36.8°, 44.9°, 55.7°, 59.2° and 65.2°, which can be identified as cubic spinel phase belonging to the space group (JCPDS No. 22-1084). At the same time, the high peak intensity confirms the high crystallinity of the sample. (14) Oxygen temperature programmed desorption (O2-TPD) In the O2-TPD analysis, two peaks were observed for the spinel catalysts modified with organic compounds. The peak observed between 60 and 240 °C corresponds to the oxygen on the catalyst surface, such as O 2- or O - The desorption of O2 was observed at 240 °C, while the peak observed above 240 °C corresponded to the desorption of lattice oxygen of Co3O4. The DL-alanine-modified spinel catalyst had the highest surface oxygen desorption amount. The catalyst showed a lower desorption temperature and the highest desorption amount, indicating that the recombination of O2 on the active site enhanced the desorption of O2, thereby improving the performance of selective catalytic reduction.
4. The SEM instrument model described in step (7) of claim 3 is ZEISS Gemini 300, the spectrometer model is OXFORD XPLORE30, and a Quorum SC7620 sputter coater is used for gold sputtering for 45-50 s and 10-15 mA. The gold sputtering target is a gold-palladium alloy. The accelerating voltage for morphology shooting is 2-3 kV, the accelerating voltage for energy spectrum mapping shooting is 15-16 kV, and the detector is an SE2 secondary electron detector.
5. The BET surface area and pore structure of the catalytic material are characterized using a Quantachrome AUTOSORB IQ instrument automated surface area, micropore, and chemical adsorption analyzer as described in step (11) of claim 3, wherein N2 is used as the adsorption gas and He is used as the carrier gas. The catalytic material is first degassed at 179-185°C for 6-7 hours and then adsorbed with N2 at -179--185°C.